2010
DOI: 10.1063/1.3295702
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically tunable surface plasmon resonance based on gold nanoparticles and elastic membrane polydimethylsiloxane composite

Abstract: Surface plasmon in nanoscaled materials has recently attracted a great deal of attention due to its possibility in a wide range of application. From a practical standpoint, it is desirable for the devices having a tunability of surface plasmon frequency. To achieve this goal, in this study, a composite consisting of two-dimensional gold nanoparticles array embedded in elastic polydimethylsiloxane (PDMS) membrane has been synthesized. Because the elastic PDMS membrane has a high malleability, with an external s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Active tuning has been recently demonstrated where the plasmonic properties of a nanocomposite are continuously modified by mechanic deformation of the nanoparticle-matrix system in order to change the interparticle distance and hence select different spectral absorption regions. [11][12][13] Deformable nanocomposites have been reported to show plasmonic shifts up to around 70 nm for uniaxial deformations of about 20%.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Active tuning has been recently demonstrated where the plasmonic properties of a nanocomposite are continuously modified by mechanic deformation of the nanoparticle-matrix system in order to change the interparticle distance and hence select different spectral absorption regions. [11][12][13] Deformable nanocomposites have been reported to show plasmonic shifts up to around 70 nm for uniaxial deformations of about 20%.…”
Section: 2mentioning
confidence: 99%
“…15 The functionalization of elastomeric surfaces with noble metal nanoparticles has been proposed as an alternative to obtain stretchable plasmonic nanocomposites: this approach allows a very precise control of nanoparticle size and reciprocal distance; however, surface-functionalized elastomers are quite fragile and their stability has not yet been characterized. [11][12][13] In view of applications, a fundamental issue is the stability of the nanocomposite optical properties upon cyclic strain conditions; to date, no characterization of this aspect is reported in the literature, although there are clear evidences that nanoparticles in an elastomeric matrix are a dynamic system undergoing rearrangement and reorganization upon stretching. 19 Recently, we showed that neutral metal clusters produced in the gas phase and aerodynamically accelerated by a supersonic expansion can be implanted in a Polydimethylsiloxane (PDMS) substrate to obtain a nanocomposite with superior resilience and interesting optical properties for the fabrication of stretchable and conformable reflective gratings; 20,21 this approach is called Supersonic Cluster Beam Implantation (SCBI).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Except for mechanical tuning, other tuning mechanisms offer a rather small spectral range of tuning. Mechanically tunable plasmonic structures which have already been demonstrated include metal nanoparticles embedded in a polymer matrix [9], and metal gratings [8,10] and nanovoids [11] supported by elastomers. Metal nanoparticles support only localized surface plasmons, while metal gratings support delocalized surface plasmons, but for a single polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Stretchable plasmonic structures have generated increasing interest for actively tuning optical response in a reproducible and continuous way. Through mechanical deformation of elastomeric substrates, spectral shifts in the resonance of plasmonic structures are reported, such as in nanoparticles matrix [13], gratings [14] and metal nanovoids [15]. However, most of the stretch-tunable plasmonics rely on modifying the gaps or cavities within or between the resonant elements which leads to limited working wavelengths.…”
Section: Introductionmentioning
confidence: 99%